DVB-RCS2 satellite return link : queueing model and resource allocation optimization based on game theory - Trindade, Pedro Henrique Andrade (2022)
Tese (doutorado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.